Pengaruh Harga, Kelengkapan Produk, Dan Wom (Word Of Mouth) Terhadap Kepuasan Konsumen Pada Store Jelita Cosmetic - Nurlaila Aprilliani; Muhajirin Muhajirin (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
Competition between the personal care and cosmetics industry markets is increasingly competitive, this is proven by the many types of cosmetics in circulation, both domestic and foreign production. The large number of cosmetic products on the market influences a person's attitude towards purchasing and using goods. Purchasing a product is no longer to fulfill a need but because of a desire. In addition, it was discovered that consumers decided to use certain products (cosmetics) in order to beautify themselves and to be seen well in certain communities. Beauty is the basic capital for modern women who always want to show their existence in sociality. There are many ways that women can do in their efforts to achieve the beauty they dream of.